2005 IEEE International Conference on Electro Information Technology
DOI: 10.1109/eit.2005.1627038
|View full text |Cite
|
Sign up to set email alerts
|

Hand Gesture Selection and Recognition for Visual-Based Human-Machine Interface

Abstract: A new paradigm has been proposed for gesture selection and recognition. The paradigm is based on statistical classification, which has applications in telemedicine, virtual reality, computer games, and sign language studies. The aims of this paper are (1) how to select an appropriate set of gestures having a satisfactory level of discrimination power, and (2) comparison of invariant moments (conventional and Zernike) and geometric properties in recognizing hand gestures. Two-dimensional structures, namely clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
3
Order By: Relevance
“…4, lower left). Thus the outer curve or edge function of a head will appear as an ellipsis, which can be detected by a classical correlation with predefined head patterns or invariant moments [6]. To enable a robust detection of heads from persons with different body heights, this sampling procedure starts at the top of the door ( 2m) and ends at the height of a children ( 0.8m).…”
Section: Person Countingmentioning
confidence: 99%
“…4, lower left). Thus the outer curve or edge function of a head will appear as an ellipsis, which can be detected by a classical correlation with predefined head patterns or invariant moments [6]. To enable a robust detection of heads from persons with different body heights, this sampling procedure starts at the top of the door ( 2m) and ends at the height of a children ( 0.8m).…”
Section: Person Countingmentioning
confidence: 99%
“…Most existing classification methods for hand posture belong to distance-based classifier [4] [5][10] [14]. The distance-based method calculates the distances between the input hand posture and the templates according to a certain criteria.…”
Section: Natural Hand Posture Recognition Based On Zernike Moments Anmentioning
confidence: 99%
“…As gesture is a natural and intuitive communication channel between human and robot, hand gesture recognition has been studied extensively [3][4] [5]. Analysis of hand posture contributes to further dynamic gesture recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al (2004) reported the use of cyber gloves to capture features and classify large vocabulary of signs using Fuzzy Decision trees. Recently, Chalechale and Safaei (2005) presented a Bayesian classifier using geometric and moment based properties of fingerspelling hand postures. They report a very good success rate, but they consider gestures of only single user.…”
Section: Introductionmentioning
confidence: 99%